Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1177/0899764008316054
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Multiple Cross-Sector Partnerships

Abstract: This research examines challenges associated with partnerships among a group of cross-sector organizations. The context for this study is a nonprofit organization in Canada's sport system and its numerous partners in public, nonprofit, and commercial sectors. The results reveal challenges in the areas of structure and strategy. Specifically, data uncover structural challenges with respect to problems with governance, roles, and responsibilities guiding the partnerships and with the complexity of partnership fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
171
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(184 citation statements)
references
References 37 publications
5
171
1
2
Order By: Relevance
“…Others point out the inherent difficulties in introducing the new collaboration forms and identify related challenges such as distrust, managerial complexity, cultural conflicts, power imbalance, risk of dependence, and lack of incentive for collaboration (e.g. Babiak and Thibault, 2009;Gazley andBrudney2002, Wondolleck andYaffee, 2000;Young, 2000). E-government refers to the use of the ICT in public administration, particularly for the purpose of communicating and exchanging information with citizens, businesses, or other governmental organizations.…”
Section: Public Sector Collaborationsmentioning
confidence: 99%
“…Others point out the inherent difficulties in introducing the new collaboration forms and identify related challenges such as distrust, managerial complexity, cultural conflicts, power imbalance, risk of dependence, and lack of incentive for collaboration (e.g. Babiak and Thibault, 2009;Gazley andBrudney2002, Wondolleck andYaffee, 2000;Young, 2000). E-government refers to the use of the ICT in public administration, particularly for the purpose of communicating and exchanging information with citizens, businesses, or other governmental organizations.…”
Section: Public Sector Collaborationsmentioning
confidence: 99%
“…However, there is a lack of methodologies within the current sport and physical activity partnership literature that facilitate assessments of associations between the multiple dimensions of partnership. For example, although Babiak and Thibault (2009) highlight key challenges to partnership working including environmental constraints, communication and managing perceived power imbalances between non-profit, public and private organisations delivering sport services in Canada, the authors do not extend their research to investigate the theoretical interrelatedness of these aspects with any identifiable outcomes. Furthermore, while the theoretical framework devised by Frisby et al (2004) is useful for investigating management issues in sport-focused partnerships, the qualitative approach limits the potential to assess associations between partnership dimensions, thus leaving questions concerning the interrelatedness of partnership processes and outcomes.…”
Section: Research Into Partnerships For Sport and Physical Activitymentioning
confidence: 99%
“…While it is difficult to argue against the 'what works' approach offered by multi-agency partnerships (Fenwick et al 2012), partnership represents a complex and confusing interplay between processes, activities and outcomes (Hunter and Perkins, 2012). This can create significant challenges for those working in partnerships who are often lacking in the skills to collaborate effectively (Halliday et al 2004;Misener and Doherty, 2009), the results of which can lead to wasted resources and partnership destruction (Babiak and Thibault, 2009). Hence, research has been critical both of the likelihood that partnerships can simultaneously achieve efficiency, effectiveness, and community empowerment, and the lack of attention being paid to the potential drawbacks (Fenwick et al 2012;Glasby et al 2006;McLaughlin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, to a great extent, the necessity of IORs has only been recognised in the sport system in recent years (e.g. Babiak and Thibault 2009, Misener and Doherty 2009, Parent and Harvey 2009, Wicker et al 2013. Robinson et al (2000) have identified three ideal types of IORs: coordination, cooperation and competition.…”
Section: Literature Review: Iors and Conflicting Objectivesmentioning
confidence: 99%